Pengaruh Profitabilitas Dan Solvabilitas Terhadap Pertumbuhan Laba Pada PT Bank Rakyat Indonesia (persero) TBK Di Bursa Efek Indonesia Periode 2018-2022 - Apolinaris S. Awotkay; Yumiad Fernando Richard; Semuel Batlajery; Simon Siamsa; Irfan Wildzan Muafa; Vincensia Fristanti Sudarsono (Nusantara Journal of Multidisciplinary Science, 2024)
This study aims to determine the influence of profitability and solvency on profit growth at PT Bank Rakyat Indonesia (Persero) Tbk. Profitability is projected by ROA, and solvency is projected by DER as independent variables, while profit growth is projected by CR as the dependent variable. The population in this study consists of the Annual Financial Statements of PT Bank Rakyat Indonesia (Persero) Tbk listed on the Indonesia Stock Exchange for the period 2018-2022. The sample in this study includes financial statement data consisting of balance sheets and income statements for the last 5 years from 2018-2022. This research uses a quantitative approach. The source of data is secondary data. The analytical tool used is multiple regression analysis at a 5% significance level using SPSS version 27. The results of this study indicate that profitability projected by ROA does not have a positive and significant influence on profit growth. Furthermore, solvency projected by DER does not have a positive and significant influence on profit growth. Simultaneously, profitability and solvency show no significant influence on profit growth.